2017
DOI: 10.1016/j.socscimed.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of sex partner meeting places reported by HIV-infected MSM: Opportunities for HIV targeted control

Abstract: Baltimore, Maryland ranks among U.S. cities with the highest incidence of HIV infection among men who have sex with men (MSM). HIV screening at sex partner meeting places or venues frequented by MSM with new diagnoses and/or high HIV viral load may reduce transmission by identifying and linking infected individuals to care. We investigated venue-based clustering of newly diagnosed MSM to identify high HIV transmission venues. HIV surveillance data from MSM diagnosed between October 2012-June 2014 and reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…The approach utilizing venue co-affiliation analyses inherently recognizes that sex partner meeting places form a network of venues, i.e. individuals attend more than one venue, which may yield important information for the optimization of public health control strategies [22][23][24][25]27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach utilizing venue co-affiliation analyses inherently recognizes that sex partner meeting places form a network of venues, i.e. individuals attend more than one venue, which may yield important information for the optimization of public health control strategies [22][23][24][25]27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is notable that the majority of nominated sex partner meeting places (53.1%) were online venues. Our prior work showed increasing trends in nominations of online sex partner meeting places, but also suggested that physical places remained important and highly connected to online spaces [ 22 , 34 ]. Our current work suggests that sex partner meeting venues are dynamic and for MSM, may be increasingly online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSN app eligibility criteria: We selected the GSN app most frequently nominated as a sex partner meeting place by newly HIV diagnosed MSM. A description of these data has been provided previously in detail 20,21 ; briefly, we used local city health department public health surveillance data from October 2012 through December 2014 of MSM newly diagnosed with HIV living in Baltimore City. Cases were considered to be MSM if during the partner services interview they self-identified as gay/bisexual or reported having sex with men.…”
Section: Methodsmentioning
confidence: 99%
“…A figure was designed using Cytoscape (Cytoscape Consortium, New York, NY) in order to provide a visual structure to the complex interactions between substance use, CAI, and the location where sex occurred, which cannot be clearly described by text or depicted in tables. Examining network connections among locations in this way yields a rarely considered additional level of information, identifying locations with high frequency of CAI and other risk behaviors that are highly connected [31].…”
Section: Methodsmentioning
confidence: 99%